THE EFFECT OF USING FRINTZ’ BRAIN AND CROSSWORD PUZZLE ON VOCABULARY MASTERY FOR STUDENTS WHO HAVE DIFFERENCE LEARNING STYLE - Aini Husnida Wulandari (SOLID, 2019)
The objective of this research is to investigate: (1) the different of students’ vocabulary mastery between those who were taught trough frintz’ brain and those who were taught through crossword puzzle, (2) the different of auditory and visual students’ vocabulary mastery, (3) the interaction between teaching methods and learning style with students vocabulary mastery, (4) which method is more effective to improve auditory students’ vocabulary mastery, and (5) which method is more effective to improve visual students’ vocabulary mastery.The research was conducted at SDN Kramatjati 27 Pagi which is located at Jl. Kerja Bakti No. 01 East Jakarta from March 2016 to June 2016. The writer took the third grade students as her research participant. There were two classes at that school. Therefore, the writer took two classes as her research with 30 students in the grade III A and 30 students in the grade IIIB. The method of the research was a quasi experiment. The data were analyzed by two-way ANOVA..Based on the results of the data analysis, there were five conclusions drawn: first, there is significant difference of students’ vocabulary mastery between those who were taught trough frinz’ brain and those who were taught trough crossword puzzle. It was supported by the p-value of methods is smaller than 0.05. Second, there is significant difference result between auditory and visual students’ on their vocabulary mastery. It was supported by p-value of learning style that is smaller than  0.05. Third, there is significant interaction between vocabulary methods and learning style on students’ vocabulary mastery. It is supported by the p-value of interaction which is smaller than 0.05. Fourth, frintz’ brain is better crossword puzzle for auditory students on their vocabulary mastery at the third grade students of Elementary School. It is supported by the mean of frintz’ brain in auditory 80.60 that is higher than the mean of crossword puzzle in auditory 75.53. Keywords: Vocabulary mastery, Frintz’brain, Crossword puzzle, Auditory and visual learning style.